Non-Orthogonal Multiple Access for Hybrid RIS-UAV-Assisted Communication (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Reconfigurable Intelligent Surfaces (RIS) have gained increasing attention for the ability to manipulate the propagation environment intelligently. When integrated with Unmanned Aerial Vehicles (UAV), forming a RIS-UAV system, the RIS can be deployed flexibly and provide improved coverage, especially in challenging communication environments. In this paper, we focus on a hybrid RIS-UAV system that combines both passive and active elements to improve the system performance. The achievable rate performance of the hybrid RIS-UAV system is investigated under two cooperative Non-Orthogonal Multiple Access (NOMA) transmission schemes: a conventional NOMA scheme with fixed power allocation based on user channel conditions, and a cognitive radio-inspired NOMA (CR-NOMA) scheme where power allocation prioritized the Quality-of-Service (QoS) requirements of the primary user. The achievable rate performance is analyzed through extensive Monte Carlo simulations. The results demonstrate that dynamic power allocation in CR-NOMA significantly outperforms the fixed power allocation in conventional NOMA, showcasing the potential of hybrid RIS-UAV system for serving multiple users with adaptive power allocation.
Keywords: Multiuser Communication; Non-Orthogonal Multiple Access; Reconfigurable Intelligent Surfaces; Unmanned Aerial Vehicles